SERVQUAL (Service Quality) vs NPS (Net Promoter Score) : A Comparative Study of Private and Public Hospitals in Sikkim - Singh, Ankit; Tewari, Ekta; Ravi, Priya (Indian Journal of Marketing, 2020)
Background : This study is the first of its kind, which has used the SERVQUAL model in conjunction with the Net Promoter Score approach to compare the service delivery of a private and a public hospital in the Himalayan state of Sikkim. Methods : The study was cross-sectional and causal, carried out from March – June 2018. This study has used the SERVQUAL gap model given by Parasuraman, Berry, and Zeithaml with the Net Promoter Score approach given by Reichheld. The statistical tools used in this study are mean, Cronbach's alpha, and independent sample t-test. The statistical packages used are MS EXCEL 2016 and SPSS V. 17. Results : A statistical significant difference was found for the tangibility and empathy dimensions between the public and private hospitals, where the service quality gap score was higher for the public hospital in both the dimensions. The Net Promoter Score for the public hospital was –3% and in case of the private hospital, the NPS was 18%. Conclusion : This study concludes that both the hospitals needed improvement ; however, the private hospital needed improvement, especially in the responsiveness, reliability, and assurance dimensions ; whereas, the public hospital needed improvement in all the five dimensions of SERVQUAL. This study also concludes that SERVQUAL and NPS approaches should not be looked as competing approaches, but these two approaches shall be used in conjunction to get a better understanding of the problem areas.